Monday Club building payment no. 2 - Julia Morgan::::::::: (1933)
Receipt and statement of contracts, payments, and deductions, issued by Julia Morgan to James J. Jepson. The payment documented in this receipt amounts to $356.50, and was paid for the 'Monday Club building as follows: Labor as per invoice December 12th ($151.00) and Invoice C. A. Phenegar ($205.50).'